Determination of the electronic concentration in a bright solar prominence - Venglinsky, E.R.; Kostenko, L.M. (Кинематика и физика небесных тел, 2005)
A spectrum of a bright prominence on April 1, 1970 is analysed. The prominence partly projected onto the solar disc near the limb where many emissive spectral lines were observed. The spectral intensity distributions in prominence and outside it were compared to derive the pure emission of prominence. Such obtained observed spectra were compared with theoretical ones calculated for the spectral region from the 18th Balmer line to series limit, and for different electronic concentrations. It was found that reliable determined electronic concentrations were in the range 10¹⁷–10¹⁸ m⁻³, i.e., 3–4 order more than in quiet solar corona. It is argued that our method for the electron concentration determination is more reliable than one proposed before by Kurochka [3], based on the analysis of the intensity increase of the continuum spectra in range of the Balmer pre-continuum.